A REVIEW OF THE POLISH EPIGRAPHY IN THE CAUCASUS - Adamcevskij, Psemyslav (History, Archeology and Ethnography of the Caucasus, 2021)
The paper attempts to compile the material, related to the Polish epigraphy in the Caucasus as its earliest monuments; to elaborate on the context of its origin and current state. The analysis of sources, such as diaries of Poles who were in the Caucasus in the 19th century, is used as the main research method.Polish epigraphy in the Caucasus can be divided into four categories: inscriptions on temples, epitaphs, advertising epigraphs, and graffiti, especially the style-writing one. The emergence of the Polish epigraphy in the region is primarily due to the division of the Polish–Lithuanian Commonwealth in the second half of the 18th century. As a result, a number of Polish soldiers who served in the imperial army, found themselves in the Caucasus. Among them were volunteers, recruits, as well as political exiles. The author of one of the most interesting recollections from the period of his service in the Caucasus, Mateusz Gralewski, belonged to the latter. He wrote that some Polish soldier allegedly found a stone with a Latin inscription Polonus Joannes Dembovscius fecit 1618 in a mosque near Shamakhi. Thus, it may be the earliest epigraphic monument in the Caucasus, related to Poland and the Poles. However, due to the fact that the information about this inscription has not been confirmed, it should be treated with skepticism.Most of the Polish inscriptions of the 19th century in the Caucasus are associated with churches and cemeteries. Many of them were destroyed and have not survived to this day, with some exceptions.In the 21st century, Polish epigraphy in the Caucasus is mainly represented by the tourist-oriented advertising. For this reason, it is often found in Georgia, which is the most developed tourist country in this part of the world.
Keywords: Poles in the Caucasus; Catholicism; Polish epigraphy; Caucasus history; Polish monuments in the Caucasus.; Polish graves in the Caucasus; political exiles in the Caucasus.